The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5121/ijite.2016.5201
|View full text |Cite
|
Sign up to set email alerts
|

Student's Patterns of Interaction with a Mathematics Intelligent Tutor: Learning Analytics Application

Abstract: Purpose: The purpose of this paper is to determine potential identifiers of students ' academic Findings: The data-logs of ALEKS include information about number of topics practiced and number of topics mastered by each student. Prior knowledge and derived attribute, which is the ratio of number of topics mastered to number of topics practiced(denoted by the variable m top in this paper) are found to be predictors of final marks in the foundation mathematics course with= 42%.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…The ALEKS web-based program is an ITS that is designed to apply mathematical instruction and ongoing assessments to monitor and manage students' knowledge acquisition. Similar to other ITSs, the computer platform gathers data related to learners' working behavior pattern and provides appropriate feedback and guidance to support their learning needs (Dani, 2016). Educationalists can obtain and apply this data to differentiate instruction to address the needs of students.…”
Section: Aleksmentioning
confidence: 99%
See 2 more Smart Citations
“…The ALEKS web-based program is an ITS that is designed to apply mathematical instruction and ongoing assessments to monitor and manage students' knowledge acquisition. Similar to other ITSs, the computer platform gathers data related to learners' working behavior pattern and provides appropriate feedback and guidance to support their learning needs (Dani, 2016). Educationalists can obtain and apply this data to differentiate instruction to address the needs of students.…”
Section: Aleksmentioning
confidence: 99%
“…U.S. high school graduates are among these nonproficient math learners, with many requiring remediation in higher education, according to Johnson and Samora (2016). The rapid infusion of intelligent tutoring systems (ITS) in high school mathematics courses has provided educators with unprecedented opportunities to engage learners in active learning (Dani, 2016;Fine et al, 2009;Icoz et al, 2015;Liu, Rogers and Pardo, 2015b) and potentially address nonproficiency issues. Such online learning platforms aid teachers with assessing, instructing, monitoring, modifying, and differentiating instruction to address the diverse needs of students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As established in the previous research [16] students who followed systematic study habits and interact with the intelligent tutor in an organized manner are more engaged in their learning. Taking notes, reading explanation are some of the systematic habits of studying and organizing learning tasks, setting goals are some of the systematic habits of using the intelligent tutor.…”
Section: Research Context and Methodologymentioning
confidence: 95%
“…Further, they attempt to accomplish these goals by organizing their learning activities. It was found that students may enjoy learning with intelligent tutors, but in order to retain the mastery of their learning, they need to organize their learning activities as suggested by the theory of self-regulated learning [16].…”
Section: Introductionmentioning
confidence: 99%